Development Cooperation Competence from the Perspective of Finnish Expatriates - Faarinen, Henna (2020)
The Thesis contributes to the ongoing discussions on professionalization in third sector in general and in development non-governmental organizations (NGDOs) in particular. This Thesis investigates what this professionalization means in terms of development cooperation competence, and explores the perspective of Finnish expatriates working in developing countries.